Investigation of Caring Behavior and Caring Burden and Their Associated Factors among Nurses Who Cared for Patients with COVID-19 in East Guilan, the North of Iran - Azar Darvishpour; Shiva Mahdavi Fashtami (Nursing Research and Practice)
Background. Nurses experience caring burdens, which can affect their caring behaviors. Caring for highly infectious patients, in particular COVID-19, is a new phenomenon and little is known about it. Considering that caring behaviors can be influenced by various factors and cultural differences of the society, it is necessary to conduct studies about caring behaviors and caring burdens. Thus, this study aimed to determine caring behavior and caring burden and their relationship with some associated factors among nurses who cared for patients with COVID-19. Materials and Methods. This cross-sectional, descriptive design study was conducted by census sampling on 134 nurses working in public health centers in East Guilan, the north of Iran, in 2021. The research instruments included the Caring Behavior Inventory (CBI-24) and the Caregiver Burden Inventory (CBI). Descriptive and inferential statistics were used to analyze the data using SPSS software version 20 with a significant level of 0.05. Results. The mean score of caring behavior and caring burden in nurses was 126.50 (SD = 13.63) and 43.65 (SD = 25.16), respectively. There was a significant relationship between caring behavior and some demographic characteristics (education, place of living, and history of COVID-19) and between caring burden and some demographic characteristics (housing status, job satisfaction, intention to change job, and history of COVID-19) (p < 0.05). Conclusions. Findings showed that despite the new emergence of COVID-19, the caring burden on nurses was moderate and they had good caring behavior. Despite these results, it is necessary for the relevant managers to pay special attention to protecting health workers during a national crisis such as COVID-19 so that they experience less caring burden and improve caring behavior.